2021
DOI: 10.1186/s12916-021-01945-2
|View full text |Cite
|
Sign up to set email alerts
|

Excess mortality for care home residents during the first 23 weeks of the COVID-19 pandemic in England: a national cohort study

Abstract: Background To estimate excess mortality for care home residents during the COVID-19 pandemic in England, exploring associations with care home characteristics. Methods Daily number of deaths in all residential and nursing homes in England notified to the Care Quality Commission (CQC) from 1 January 2017 to 7 August 2020. Care home-level data linked with CQC care home register to identify home characteristics: client type (over 65s/children and adul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(75 citation statements)
references
References 21 publications
2
72
0
1
Order By: Relevance
“…Due to these methodological constraints, this study was designed as a crosssectional analysis of the population of residents who were living in a care home before the onset of the COVID-19 pandemic, with an adjustment for the time spend in a care home. A caveat to extrapolating these findings to the current population of care home residents is therefore that there may have been systemic changes in resident characteristics, due to the uneven impact of COVID-19 mortality across care homes, changes in care home occupancy levels or the influx of new residents [3,37,38]. While the study cohorts were comparable in observed characteristics, another limitation of observational studies is that unobserved differences between study cohorts or hospital records could have confounded the estimates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to these methodological constraints, this study was designed as a crosssectional analysis of the population of residents who were living in a care home before the onset of the COVID-19 pandemic, with an adjustment for the time spend in a care home. A caveat to extrapolating these findings to the current population of care home residents is therefore that there may have been systemic changes in resident characteristics, due to the uneven impact of COVID-19 mortality across care homes, changes in care home occupancy levels or the influx of new residents [3,37,38]. While the study cohorts were comparable in observed characteristics, another limitation of observational studies is that unobserved differences between study cohorts or hospital records could have confounded the estimates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Excess mortality attributable to COVID-19 in care homes in England up to 7th August 2020 has been estimated to be equivalent to 6.5% of care home beds [3].…”
Section: Comparison With Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these methodological constraints, this study was designed as a cross-sectional analysis of the population of residents who were living in a care home before the onset of the COVID-19 pandemic, with an adjustment for the time spend in a care home. A caveat to extrapolating these findings to the current population of care home residents is therefore that there may have been systemic changes in resident characteristics, due to the uneven impact of COVID-19 mortality across care homes, changes in care home occupancy levels or the influx of new residents [3,38,39]. While the study cohorts were comparable in observed characteristics, another limitation of observational studies is that unobserved differences between study cohorts or hospital records could have confounded the estimates.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…9 Analysis of data reported to the Care Quality Commission (CQC) in England suggested that excess deaths represented about 6.5% of care home beds. 10 Care home residents typically have multiple risk markers for Covid-19 vulnerability, but the transmission of Covid-19 may also have been facilitated in the care home environment and outbreaks were frequent. However, rigorous epidemiological analysis has been limited and few studies included denominator data, case-mix variables or population controls.…”
Section: Introductionmentioning
confidence: 99%